ChemInform Abstract: Synthesis and Biological Evaluation of a Phosphonate Phosphoantigen Prodrug. Issue 39 (September 2015) - Hsiao, Chia‐Hung Christine; Lin, Xiaochen; Barney, Rocky J.; Shippy, Rebekah R.; Li, Jin; Vinogradova, Olga; Wiemer, David F.; Wiemer, Andrew J.
Abstract Review: 7 refs.